Photocatalytic Degradation of Crystal Violet Using CuFe₂O₄ in a Heterogeneous Photo-Fenton System with Ascorbic Acid - Apri Rahmanisa; Indang Dewata; Mawardi; Romy Dwipa Yamesa Away (Universitas Pendidikan Mandalika, 2026)
Crystal violet is a persistent dye that is difficult to remove using conventional treatment methods. This study investigates the degradation of crystal violet using a CuFe₂O₄-based heterogeneous photo-Fenton system in the presence of ascorbic acid. The novelty of this work lies in the combined use of CuFe₂O₄ and ascorbic acid to enhance redox cycling and improve degradation performance under photo-Fenton conditions. The CuFe₂O₄ catalyst was synthesized via a sol–gel method and characterized using Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD), confirming the formation of a spinel structure with an average crystallite size of 38.4 nm. The degradation process was evaluated by varying pH (1–9) and hydrogen peroxide (H₂O₂) concentration (10–50 mmol/L). The optimum pH was found to be 3, achieving a degradation efficiency of 94.38%, while the optimum H₂O₂ concentration was 30 mmol/L with a degradation efficiency of 93.56%.The improved degradation performance is attributed to enhanced hydroxyl radical (•OH) generation facilitated by the interaction between CuFe₂O₄ and ascorbic acid. These results suggest that CuFe₂O₄ with ascorbic acid can improve crystal violet degradation under the tested photo-Fenton conditions.